DAMPAK COVID-19 TERHADAP KINERJA DAN MANAJEMEN SUMBER DAYA DOSEN - Sutangsa, Sutangsa; Lysda Reviyanti, Lysda Reviyanti (Edum Journal, 2021)
DAMPAK COVID-19 TERHADAP KINERJA DAN MANAJEMEN SUMBER DAYA DOSEN Sutangsa dan Lysda Reviyanti sutangsapls@gmail.com dan lysdarevi@gmail.com Universitas Subang dan Universitas Halim Sanusi PUI ABSTRAK The impact of the pandemic has disrupted the learning process for higher education in Indonesia. The purpose of this study was to determine the impact of COVID-19 on lecturer performance and resource management. This research was conducted at the University of Subang on Jl. R.A. Kartini KM. 3 villages of Nyimplung, Pasirkareumbi, Kec. Subang, Subang Regency, West Java 41285. This study used a qualitative research method with a case study approach. During the COVID-19 pandemic at the University of Subang, the lecturers' performance was less effective. It can be seen that lecturers teach not face-to-face but online. Lecturers give online lectures using Zoom, Google Classroom and Whatsapp Group. The use of Zoom and Google Meet media when delivering material to students is not without obstacles. Often, when online lectures are taking place, the internet network can be cut off or the signal is weak, and even the internet quota runs out, whether it happens to lecturers or students. Zoom technology which is free also has a time limit, and Google Meet also has a limit in the number of users. The biggest challenge when giving lectures online for approximately three months is how to know that the material we convey is sufficiently accepted and understood by students. Human Resource Management (MSDM) in the COVID-19 era at the University of Subang, namely (1) HR management, which must present a professional lecturer profession where the final output of the campus is able to produce graduates who are competent in their respective fields. (2) If one of the higher education tridharma instruments is neglected by the lecturer, for example lecturers and higher education institutions merely carry out educational and teaching functions on a regular basis and ignore other functions, then the lecturers and tertiary institutions will not have the passion as a professional education provider and in turn, it will have an impact on the low work culture of lecturers and universities. (3) Human Resources Management at the University of Subang requires lecturers to have the ability, work motivation, work discipline, work ethics, work culture, work ethic, and high work morale. (4) Human Resource Management at the University of Subang, both at the top to the lowest level of leadership and staffing as academic support, must be able to work to present professional lecturers by serving all out, taking inventory of lecturers' needs, innovating for solutions, maintaining relationships. Kata Kunci : Covid-19, Kinerja Dosen, MSDM